Exploring City Brand Gestalt Driver: The Case of Bitung City - Mandagi, Deske W.; Darvel Civlie Walone; Tonny Irianto Soewignyo (SEAN Institute, 2024)
As urban landscapes evolve rapidly and competition among cities intensifies for economic growth and global recognition, the imperative to understand the dynamics of City Brand Gestalt (CBG) has heightened. This study aims to delve into the architecture of CBG by assessing the impact of its four dimensions (namely Story, Sensescape, Servicescape, and Stakeholder) on shaping Bitung City's overall brand gestalt. This research holds significance in formulating development strategies for CBG aimed at improving the economy of Bitung City, particularly in the tourism sector. A quantitative descriptive and causal research design was adopted by distributed and collected 250 self-administered online questionnaires from Bitung City visitors between January and May 2023. Structural Equation Modeling using SmartPLS was employed to determine the significant influence of each dimension on brand gestalt. The results confirmed the significant role of the 4S dimensions namely, story, sensescape, servicescape, and stakeholder in shaping the overall city brand gestalt. In summary, this research underscores significant implications for city marketers and policymakers, emphasizing the necessity of crafting an appealing and positive brand narrative to enhance the image of a city. This, in turn, can bolster the city's economy, particularly in terms of tourism and other sectors.